2022
DOI: 10.1002/nop2.1292
|View full text |Cite
|
Sign up to set email alerts
|

Psychological support and demand for death education among Chinese college students during the COVID‐19 pandemic: The mediating role of neutral death attitude

Abstract: Aim This study aimed to explore the mediating role of neutral death attitude between psychological support and demand for death education among college students during COVID‐19. Design A cross‐sectional survey was conducted with 1800 college students selected by convenience and snowball sampling from 20 provinces and municipalities. Methods A questionnaire survey (The Psychological Support Scale, Demand for Death Education Scale and Neutral D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 88 publications
0
9
0
Order By: Relevance
“…The release of this film also demonstrated the gradual opening up of young Chinese people's attitudes towards death, as the film was also a way of open discussion that could reflect the culture and shape ideas (Rosenstone, 1986). The pandemic forced many teenagers to face bereavement unprepared and forced them to confront death directly, but they still had a very vague idea of what death was (Jiang, 2022). The film is good teaching material.…”
Section: Possible Teaching Methodsmentioning
confidence: 95%
“…The release of this film also demonstrated the gradual opening up of young Chinese people's attitudes towards death, as the film was also a way of open discussion that could reflect the culture and shape ideas (Rosenstone, 1986). The pandemic forced many teenagers to face bereavement unprepared and forced them to confront death directly, but they still had a very vague idea of what death was (Jiang, 2022). The film is good teaching material.…”
Section: Possible Teaching Methodsmentioning
confidence: 95%
“…This conclusion is consistent with existing research: Otsuka et al ( 64 ) identified an association between instrumental social support and emotional social support with a reduced risk of suicide. Jiang’s study showed that psychological support had a prominent positive predictive effect on death education demand and neutral death attitude ( 65 ). On this basis, it is suggested that improving social support can facilitate Chinese parents forming a positive and healthy attitude toward death and increase their demand and support for death education (note that demand in this context can also be seen as this support).…”
Section: Discussionmentioning
confidence: 99%
“…At present, more than 20 colleges and universities, including Peking University and Guangzhou University, have offered courses related to death education. The relevant courses guide students to face death and revere life flexibly and diversely [9].…”
Section: Arrangements Of Death Education Curriculummentioning
confidence: 99%